Spatial planning and land-use management - Gomes, Eduardo (2024)
Spatial Planning and Land-Use Management play a pivotal role in striking a balance between enhancing the quality of life for communities and addressing environmental protection and natural resource management. Additionally, they facilitate the exploration of alternative land-use scenarios that cater to socioeconomic, cultural, and environmental needs, ensuring the welfare of populations while upholding principles of efficiency, equity, and sustainability. Recognizing the enduring impact of spatial planning and land-use management on the future trajectory of societies, it is imperative to establish optimal systems and tools in the present day. This is particularly crucial in regions poised for swift increases in demand for housing, infrastructure, services, and food. A strategic redirection of measures towards a more inclusive and system-oriented territorial development emerges as a potentially effective approach.The purpose of the Special Issue "Spatial Planning and Land-Use Management" is to highlight the latest advancements in this field. It presents case studies from three continents: Europe, South America, and Asia. The articles can assist policymakers in making well-informed decisions by providing valuable insights that contribute to the formulation of more sustainable land-use practices.